Thermally crosslinkable and chemically modifiable aromatic polyesters possessing pendant propargyloxy groups - Verma, Savita; Maher, Deepak M.; Nagane, Samadhan S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer-catalyzed interfacial polycondensation of 5-(propargyloxy)isophthaloyl chloride (P-IPC) and various compositions of P-IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran and could be cast into transparent, flexible, and tough films from chloroform solution. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.77-1.33 dL/g and 43,600-118,000 g/mol, respectively, indicating the achievement of reasonably high-molecular weights. The 10% weight loss temperatures of (co)polyesters were in the range 390-420 degrees C, demonstrating their good thermal stability. (Co)polyesters exhibited T-g in the range 146-170 degrees C and T-g values decreased with increase in mol % incorporation of P-IPC. The study of non-isothermal curing by DSC indicated thermal crosslinking of (co)polyesters via propargyloxy groups. The utility of pendant propargyloxy group was demonstrated by post-modification of the selected copolyester with 1-(4-azidobutyl)pyrene, 9-(azidomethyl)anthracene, and azido-terminated poly(ethyleneglycol) monomethyl ether via copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction. FTIR and H-1 NMR spectra confirmed that click reaction was quantitative. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 588-597
Keywords: Click chemistry; crosslinking; modification; polyesters; propargyloxy; step-growth polymerization